Neural circuits for the adaptive regulation of fear and extinction memory - Plas, Samantha L.; Tuna, Tuğçe; Bayer, Hugo; Juliano, Vitor A. L.; Sweck, Samantha O.; Arellano Perez, Angel D.; Hassell, James E.; Maren, Stephen (Frontiers in Behavioral Neuroscience, 2024)
The regulation of fear memories is critical for adaptive behaviors and dysregulation of these processes is implicated in trauma-and stress-related disorders. Treatments for these disorders include pharmacological interventions as well as exposure-based therapies, which rely upon extinction learning. Considerable attention has been directed towards elucidating the neural mechanisms underlying fear and extinction learning. In this review, we will discuss historic discoveries and emerging evidence on the neural mechanisms of the adaptive regulation of fear and extinction memories. We will focus on neural circuits regulating the acquisition and extinction of Pavlovian fear conditioning in rodent models, particularly the role of the medial prefrontal cortex and hippocampus in the contextual control of extinguished fear memories.We will also consider new work revealing an important role for the thalamic nucleus reuniens in the modulation of prefrontal-hippocampal interactions in extinction learning and memory.Finally, we will explore the effects of stress on this circuit and the clinical implications of these findings.